INTERACTIVE METHODS OF TEACHING LANGUAGE SKILLS - Bakhronova Zulfiya Ravshanovna,; Rasulova Muhabbat Ixtiyorovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This work is aimed at developing all the skills of students in teaching foreign languages through interactive methods. Thus, the research topic is called “Interactive Methods of Teaching Language Skills”. The study discusses the importance of perfectly organizing all skills in foreign language teaching. Modern methods and interactive methods will be carefully studied and applied. It is also important to increase the effectiveness of foreign language learning using modern methods, away from traditional teaching methods, and to use it as an effective teaching tool in the formation of language learning skills. The aim of the research is to provide foreign language teachers with a brief overview of the interactive methods used at different stages of language skills development, especially the various tools aimed at developing students ’cognitive skills.